Factors That Influence the Relationship Between Social Support and Health-Related Quality of Life of Older People Living in the Community - Sarla, Efstathia; Lambrinou, Ekaterini; Galanis, Petros; Kalokairinou, Athena; Sourtzi, Panayota (My University, 2020)
As the proportion of older people in Greece grows and the need for promoting healthy aging is apparent, it becomes increasingly important to investigate the relationship between social support and health-related quality of life (HRQoL) of older people in the community. A cross-sectional study was conducted in 451 older people living in the community in greater Athens, Greece, with an anonymous questionnaire, including demographics, and the EQ5D including EuroQol-visual analogue scale (EQ-VAS) and the Multidimensional Scale of Perceived Social Support. Multivariate linear regression analysis was applied to identify independent factors related to perceived social support and HRQoL. The majority of older people were women, married or widowed, living with their family or alone. Perceived social support was medium and higher from significant others and family. A statistically significant positive relationship was found between social support from significant others/friends and HRQoL, as well as between social support from friends/family/significant others and EQ-VAS. In conclusion, HRQoL of older people is influenced by the received social support.
Keywords: Community; Family; Health-related quality of life; Older people; Social support